Computer-Based Learning: The Use of SPSS Statistical Program for Improving Biostatistical Competence of Medical Students. (22nd October 2014) - Perry, Zvi H.; Barak, Aricha-Tamir; Neumann, Lily; Levy, Amalia
Abstract : Background . We changed the biostatistics curriculum for our medical students and have created a course entitled "Multivariate analysis of statistical data, using the SPSS package." Purposes . The aim of this course was to develop students' skills in computerized data analysis, as well as enhancing their ability to read and interpret statistical data analysis in the literature. Methods . In the current study we have shown that a computer-based course for biostatistics and advanced data analysis is feasible and efficient, using course specific evaluation questionnaires. Results . Its efficacy is both subjective (our subjects felt better prepared to do their theses, as well as to read articles with advanced statistical data analysis) and objective (their knowledge of how and when to apply statistical procedures seemed to improve). Conclusions . We showed that a formal evaluative process for such a course is possible and that it enhances the learning experience both for the students and their teachers. In the current study we have shown that a computer-based course for biostatistics and advanced data analysis is feasible and efficient.